Copolymer, pressure-sensitive adhesive composition, pressure-sensitive adhesive tape, and method for producing copolymer
The development of a copolymer through emulsion polymerization, specifically designed with octyl (meth)acrylate and ethylenically unsaturated compounds, addresses the challenges of adhesive strength and heat resistance in existing adhesive compositions, resulting in a robust adhesive layer with enhanced performance under varying temperatures.
Patent Information
- Application Number
- JP2024029081
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-02-28
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-02-28
AI Technical Summary
Existing adhesive compositions and adhesives face challenges with solidification during polymerization, poor emulsion formation, and inadequate adhesive strength and retention strength under high temperature environments.
A copolymer is developed through emulsion polymerization, comprising a first structural unit derived from alkyl (meth)acrylate, particularly octyl (meth)acrylate, and a second structural unit derived from an ethylenically unsaturated compound with a carboxy group or its salt, which is used to create a pressure-sensitive adhesive composition and adhesive tape.
The copolymer achieves excellent heat resistance and forms an adhesive layer with strong adhesive strength at both room and high temperatures, along with improved retention force at high temperatures.
Smart Images

Figure 0007658480000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a copolymer, a pressure-sensitive adhesive composition, a pressure-sensitive adhesive tape, and a method for producing the copolymer. [Background technology]
[0002] A typical application of adhesives is adhesive tape. Adhesive tapes usually have a layer containing an adhesive, i.e., an adhesive layer, formed on a substrate. Adhesive tapes are attached to articles, for example, to repair various articles or to fix articles together. Double-sided adhesive tapes in which adhesive layers are formed on both sides of a substrate are used in a wide range of applications, such as transportation equipment such as automobiles, home appliances such as refrigerators, mobile terminals such as notebook computers, and architectural applications such as wallpaper. These industrial applications require stricter performance requirements, such as adhesion to adherends that are very difficult to adhere to, adhesion reliability under harsh environmental conditions, and adhesion over a small area.
[0003] A typical method for manufacturing an adhesive tape is to apply a coating liquid in which an adhesive is dissolved or dispersed in a liquid medium onto a substrate, and then dry the substrate to form an adhesive layer on the substrate surface. As adhesives, for example, natural rubber-based, synthetic rubber-based, acrylic-based, etc. are widely used, and acrylic-based adhesives are particularly characterized by their ability to impart various functions. In recent years, the use of water as a liquid medium has been widely considered, taking into account environmental loads, etc.
[0004] Patent Document 1 describes a pressure-sensitive adhesive composition containing 2-octyl (meth)acrylate, a (meth)acrylic acid copolymer, and optionally a crosslinking agent.
[0005] Patent Document 2 describes a resin composition containing a homopolymer or copolymer of 1-methyl alkyl acrylate.
[0006] Patent Document 3 describes an adhesive comprising a reaction product of 2-octyl (meth)acrylate, at least partly derived from castor oil, a reaction initiator, and a stabilizer. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Special Publication No. 2011-516690 [Patent Document 2] Japanese Patent Application Publication No. 10-231325 [Patent Document 3] JP 2014-077141 A Summary of the Invention [Problem to be solved by the invention]
[0008] The adhesive composition described in Patent Document 1 solidifies during polymerization and fails to obtain an emulsion. The acrylic copolymer in Patent Document 2 and the adhesive in Patent Document 3 both have room for improvement in adhesion under high temperature conditions, and furthermore, there is room for improvement in holding power under high temperature conditions.
[0009] An object of the present disclosure is to provide a copolymer capable of forming an adhesive layer having excellent heat resistance and exhibiting strong adhesive strength, a pressure-sensitive adhesive composition and pressure-sensitive adhesive tape using the copolymer, and a method for producing the copolymer. [Means for solving the problem]
[0010] [1] A copolymer obtained by emulsion polymerization, comprising a first structural unit derived from an alkyl (meth)acrylate and a second structural unit derived from an ethylenically unsaturated compound having at least one selected from the group consisting of a carboxy group and a salt of a carboxy group, wherein the first structural unit includes a structural unit derived from octyl (meth)acrylate. [2] The copolymer according to [1], wherein the content of structural units derived from octyl (meth)acrylate among the structural units contained as the first structural units is 20 to 100 mass %. [3] The copolymer according to [2], wherein the content of structural units derived from 2-octyl(meth)acrylate among the structural units contained as the first structural units is 20 to 100 mass %. [4] The copolymer according to any one of [1] to [3], wherein the content of the second structural unit is 1.0 to 10 mass %. [5] The copolymer according to any one of [1] to [4], wherein the first structural unit further includes at least one selected from the group consisting of a structural unit derived from methyl (meth)acrylate, a structural unit derived from n-butyl (meth)acrylate, and a structural unit derived from 2-ethylhexyl (meth)acrylate. [6] The copolymer according to any one of [1] to [5], further comprising a structural unit derived from a vinyl ester compound. [7] A pressure-sensitive adhesive composition comprising the copolymer according to any one of [1] to [6] and an aqueous medium. [8] The pressure-sensitive adhesive composition according to [7], wherein the copolymer is dispersed as particles in the aqueous medium to form an emulsion. [9] The pressure-sensitive adhesive composition according to [8], wherein the particles dispersed in the aqueous medium have an average particle size of 10 to 50,000 nm.
[10] An adhesive tape comprising a substrate and an adhesive layer formed on a surface of the substrate, the adhesive layer being formed using the adhesive composition according to [7] or [8].
[11] A method for producing the copolymer according to any one of [1] to [6], comprising a step of emulsion polymerizing a monomer containing an alkyl(meth)acrylate and an ethylenically unsaturated compound having at least one selected from the group consisting of a carboxy group and a salt of a carboxy group, wherein the alkyl(meth)acrylate contains octyl(meth)acrylate.
[12] The method for producing a copolymer according to
[11] , wherein the alkyl (meth)acrylate includes 2-octyl (meth)acrylate.
[13] The method for producing a copolymer according to
[11] or
[12] , wherein the content of octyl (meth)acrylate in the monomers is 20 to 90 mass %. Effect of the Invention
[0011] According to the present disclosure, it is possible to provide a copolymer capable of forming an adhesive layer having excellent heat resistance and exhibiting strong adhesive strength, a pressure-sensitive adhesive composition and a pressure-sensitive adhesive tape using the copolymer, and a method for producing the copolymer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] In the following description, unless otherwise specified, surface means "surface."
[0013] "(Meth)acrylic" is a general term for acrylic and methacrylic, and "(meth)acrylate" is a general term for acrylate and methacrylate.
[0014] The term "ethylenically unsaturated compound" refers to a compound having an ethylenically unsaturated bond. Unless otherwise specified, the term "ethylenically unsaturated bond" refers to an ethylenically unsaturated bond having radical polymerizability.
[0015] In a polymer of an ethylenically unsaturated compound, a structural unit derived from a certain ethylenically unsaturated compound has a corresponding relationship in which the chemical structure of the part other than the ethylenically unsaturated bond of the ethylenically unsaturated compound is the same as the chemical structure of the part of the polymer other than the part corresponding to the ethylenically unsaturated bond of the structural unit. For example, a structural unit derived from acrylic acid has a structure represented by -CHCH(COOH)- in the polymer.
[0016] In the following description, the compound from which a certain structural unit originates refers to a compound that has the above-mentioned relationship with the structural unit, and does not necessarily have to be the same as the compound used in the actual manufacturing process. In cases where the chemical structure of the monomer does not correspond to the chemical structure of the polymer, such as when a part other than the chain corresponding to the ethylenically unsaturated bond is chemically reacted after polymerization, the chemical structure after polymerization is used as the basis. For example, in the case where vinyl acetate is polymerized and then saponified, the chemical structure of the polymer is used as the basis, and the structural unit of the polymer is not a structural unit derived from vinyl acetate but a structural unit derived from vinyl alcohol.
[0017] For structural units having an ionic functional group such as a carboxyl group, unless otherwise specified, the structural unit is considered to be derived from the same ionic compound, regardless of whether a part of the functional group is ion-exchanged or not. For example, a structural unit represented by -CH2C(CH3)(COONa)- is also considered to be a structural unit derived from methacrylic acid, unless otherwise specified.
[0018] The term "salt of a carboxy group" refers to a structure in which a carboxy group forms a salt, and examples thereof include -COONa, -COOK, and -COONH4.
[0019] A "dispersion" is a solid-liquid mixture in which a solid is present that is not dissolved in the liquid but is dispersed as particles in the liquid. "Slurry" refers to a fluid in which solid particles such as clay, pigments, etc. are suspended in a liquid.
[0020] In the following description, "adhesive strength" refers to the force required to peel the adhesive surface from the adherend, and "holding strength" refers to the strength of an adhesive layer constituting the adhesive surface, such as an adhesive tape, to resist slippage due to a static load applied in a direction parallel to the adhesive surface.
[0021] <1.Copolymer> The copolymer of this embodiment (hereinafter also referred to as "copolymer (A)") is obtained by emulsion polymerization. Copolymer (A) has a first structural unit derived from an alkyl (meth)acrylate and a second structural unit derived from an ethylenically unsaturated compound having at least one selected from the group consisting of a carboxy group and a salt of a carboxy group. In addition to the first structural unit and the second structural unit, copolymer (A) may have other structures that do not fall into either the first structural unit or the second structural unit. Details of the other structures will be described later.
[0022] (1-1. First structural unit) The first structural unit includes a structural unit derived from octyl (meth)acrylate. The first structural unit preferably includes at least one selected from the group consisting of a structural unit derived from n-octyl (meth)acrylate and a structural unit derived from 2-octyl (meth)acrylate, more preferably includes at least one selected from the group consisting of a structural unit derived from 2-octyl acrylate and a structural unit derived from 2-octyl methacrylate, and further preferably includes a structural unit derived from 2-octyl acrylate.
[0023] Among the structural units contained as the first structural units, the content of the structural unit derived from octyl(meth)acrylate is preferably 20% by mass or more, more preferably 40% by mass or more, and even more preferably 45% by mass or more, because the adhesive layer obtained from the adhesive composition containing the copolymer (A) has improved adhesive strength in a high-temperature environment.
[0024] Among the structural units contained as the first structural unit, the content of the structural unit derived from octyl (meth)acrylate may be 100% by mass, but may also be 90% by mass or less, 80% by mass or less, or 70% by mass or less.
[0025] Among the structural units contained as the first structural unit, the content of the structural unit derived from octyl (meth)acrylate may be 20 to 100 mass%, may be 20 to 90 mass%, may be 40 to 80 mass%, or may be 45 to 70 mass%.
[0026] Among the structural units contained as the first structural units, the content of the structural unit derived from 2-octyl(meth)acrylate is preferably 20% by mass or more, more preferably 40% by mass or more, and even more preferably 45% by mass or more, because the adhesive layer obtained from the adhesive composition containing the copolymer (A) has improved adhesive strength in a high-temperature environment.
[0027] Among the structural units contained as the first structural unit, the content of the structural unit derived from 2-octyl(meth)acrylate may be 100% by mass, or may be 90% by mass or less, 80% by mass or less, or 70% by mass or less.
[0028] Among the structural units contained as the first structural unit, the content of the structural unit derived from 2-octyl(meth)acrylate may be 20 to 100 mass%, may be 20 to 90 mass%, may be 40 to 80 mass%, or may be 45 to 70 mass%.
[0029] The first structural unit may further include a structural unit derived from an alkyl (meth)acrylate other than octyl (meth)acrylate. Examples of compounds other than octyl (meth)acrylate from which the first structural unit is derived include methyl (meth)acrylate, n-butyl (meth)acrylate, 1-methylpropyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isobutyl (meth)acrylate, isoamyl (meth)acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, and stearyl (meth)acrylate. The compounds other than octyl (meth)acrylate from which the first structural unit is derived may be one type or two or more types.
[0030] It is preferable that the first structural unit further includes at least one of a structural unit derived from methyl (meth)acrylate, a structural unit derived from n-butyl (meth)acrylate, and a structural unit derived from 2-ethylhexyl (meth)acrylate, and it is more preferable that the first structural unit further includes a structural unit derived from methyl (meth)acrylate and further includes at least one of a structural unit derived from n-butyl (meth)acrylate and a structural unit derived from 2-ethylhexyl (meth)acrylate.
[0031] The structure of the first structural unit is preferably designed according to the glass transition temperature Tg of the copolymer (A), but is not limited thereto. The method of determining the glass transition temperature Tg of the copolymer (A) and the preferred range thereof will be described later. The alkyl group contained in the first structural unit may have a linear structure or a branched structure. Here, the alkyl group contained in the first structural unit has the same structure as the alkyl group bonded to the (meth)acryloyloxy group in the alkyl (meth)acrylate constituting the first structural unit.
[0032] The number of carbon atoms in the alkyl group contained in the first structural unit may be 1 or more, 2 or more, 4 or more, or 6 or more. In addition, the number of carbon atoms in the alkyl group contained in the first structural unit may be 20 or less, 15 or less, or 10 or less. The alkyl group contained in the first structural unit may have 1-20 carbon atoms, 2-15 carbon atoms, 4-10 carbon atoms, or 6-10 carbon atoms.
[0033] (1-2. Second structural unit) The second structural unit is a structural unit derived from an ethylenically unsaturated compound having at least one selected from the group consisting of a carboxy group and a salt of a carboxy group. The number of carboxy groups or salts of carboxy groups contained in the second structural unit is not particularly limited, and may be one or two or more. Examples of compounds from which the second structural unit is derived include (meth)acrylic acid, 2-carboxyethyl (meth)acrylate, itaconic acid, maleic acid, etc. The number of compounds from which the second structural unit is derived may be one type, or two or more types.
[0034] The second structural unit preferably contains a structural unit derived from a compound having at least one selected from the group consisting of a carboxy group and a salt of a carboxy group and an acryloyl group, and more preferably contains a structural unit derived from (meth)acrylic acid. Among the structural units contained as the second structural units, the content of structural units derived from (meth)acrylic acid is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more, and may be 100% by mass.
[0035] (1-3. Other Structures) Examples of other structures that the copolymer (A) may have include other structural units that do not fall under either the first structural unit or the second structural unit (hereinafter simply referred to as "other structural units"); terminal structures derived from a polymerization initiator, a chain transfer agent, etc.; and the like.
[0036] [Other structural units] Compounds from which other structural units are derived are not particularly limited, and examples thereof include vinyl ester compounds such as vinyl acetate, vinyl formate, vinyl propionate, and vinyl versatate; conjugated diolefin compounds such as butadiene, isoprene, and chloroprene; aminimide group-containing vinyl compounds such as 1,1,1-trimethylamine methacrylimide; (meth)acrylamide compounds such as (meth)acrylamide, N-methyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, and N,N-dimethylaminopropyl(meth)acrylamide; 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, and vinyltriethoxysilane; Examples of the vinyl compounds containing an alkoxysilyl group include vinyl compounds containing an alkoxysilyl group such as vinyl tris(β-methoxyethoxy)silane, vinyl tris(β-methoxyethoxy)silane, etc.; vinyl compounds containing an epoxy group such as glycidyl (meth)acrylate, glycidyl vinyl ether, and glycidyl (meth)allyl ether, etc.; ethylenically unsaturated compounds having a carbonyl group such as diacetone acrylamide, methyl vinyl ketone, phenyl vinyl ketone, ethyl vinyl ketone, n-propyl vinyl ketone, isopropyl vinyl ketone, n-butyl vinyl ketone, and t-butyl vinyl ketone, etc.; light stabilizers having radical polymerization properties such as 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, etc.; polymerizable surfactants, etc. The compounds from which the other structural units are derived may be one type or two or more types.
[0037] When the copolymer (A) has the above-mentioned other structural units, it preferably has a structural unit derived from a vinyl ester compound, and more preferably has a structural unit derived from ethyl acetate.
[0038] When the copolymer (A) has a structural unit derived from a vinyl ester compound, the content of the structural unit derived from the vinyl ester compound in the copolymer (A) is preferably 1.0 mass% or more, more preferably 2.5 mass% or more, and even more preferably 4.0 mass% or more, since this improves the adhesive strength of the pressure-sensitive adhesive containing the copolymer (A) at room temperature.
[0039] When the copolymer (A) has a structural unit derived from a vinyl ester compound, the content of the structural unit derived from the vinyl ester compound in the copolymer (A) is preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 8.0% by mass or less, because the adhesive strength at room temperature of the pressure-sensitive adhesive containing the copolymer (A) is improved.
[0040] When the copolymer (A) has a structural unit derived from a vinyl ester compound, the content of the structural unit derived from the vinyl ester compound in the copolymer (A) may be 1.0 to 15 mass%, may be 2.5 to 10 mass%, or may be 4.0 to 8.0 mass%.
[0041] The polymerizable surfactant from which the other structural unit is derived is a compound that has an ethylenically unsaturated bond and also functions as a surfactant.The polymerizable surfactant may be nonionic, anionic, or cationic, but is more preferably anionic.The anionic polymerizable surfactant may be ether sulfate type, ether sulfate type ammonium salt, phosphate ester type, etc., and among these, ether sulfate type ammonium salt is preferred.
[0042] When the copolymer (A) has a structural unit derived from a polymerizable surfactant, the content of the structural unit derived from the polymerizable surfactant in the copolymer (A) is preferably 0.10% by mass or more, more preferably 0.30% by mass or more, and even more preferably 0.60% by mass or more, in order to further improve the dispersion stability of the copolymer (A).
[0043] When the copolymer (A) has a structural unit derived from a polymerizable surfactant, the content of the structural unit derived from the polymerizable surfactant in the copolymer (A) is preferably 5.0 mass% or less, more preferably 3.0 mass% or less, and even more preferably 1.5 mass% or less, in order to more effectively obtain the intended function of the copolymer (A).
[0044] When the copolymer (A) has a structural unit derived from a polymerizable surfactant, the content of the structural unit derived from the polymerizable surfactant in the copolymer (A) may be 0.10 to 5.0 mass%, may be 0.30 to 3.0 mass%, or may be 0.60 to 1.5 mass%.
[0045] The copolymer (A) may further have structural units other than the structural units exemplified above.
[0046] [Terminal structure] The copolymer (A) may have a terminal structure derived from a polymerization initiator, a chain transfer agent, or the like. The content of the terminal structure in the copolymer (A) is preferably 0.50 parts by mass or less per 100 parts by mass of the total amount of the structural units contained in the copolymer (A). When the content of the terminal structure in the copolymer (A) is 0.50 parts by mass or less per 100 parts by mass of the total amount of the structural units contained in the copolymer (A), the presence of the terminal structure may be ignored in calculating the content of each structural unit. The polymerization initiator and the chain transfer agent from which the terminal structure is derived will be described in detail later.
[0047] (1-4. Content of each structural unit in copolymer (A)) The content of the first structural unit in the copolymer (A) is preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, because this can suppress an increase in the glass transition point of the copolymer (A) and improve the tackiness, wettability, and further adhesive strength of the adhesive layer.
[0048] The content of the first structural unit in the copolymer (A) is preferably 99% by mass or less, more preferably 98% by mass or less, and even more preferably 97% by mass or less, because the polarity of the copolymer (A) and the cohesive strength of the adhesive layer are appropriately maintained, and an adhesive layer having high adhesiveness not only at room temperature but also at high and low temperatures can be obtained.
[0049] The content of the first structural unit in the copolymer (A) may be 60 to 99 mass %, 70 to 98 mass %, or 80 to 97 mass %.
[0050] The content of the second structural unit in the copolymer (A) is preferably 1.0% by mass or more, more preferably 2.0% by mass or more, and even more preferably 3.0% by mass or more, because this can improve the cohesive strength of the adhesive layer containing the copolymer (A) and increase the holding power at high temperatures.
[0051] The content of the second structural unit in the copolymer (A) is preferably 10% by mass or less, more preferably 7.0% by mass or less, and even more preferably 5.0% by mass or less, because this can suppress an increase in the glass transition point of the copolymer (A) and improve the tackiness, wettability, and further adhesive strength of the adhesive layer.
[0052] The content of the second structural unit in the copolymer (A) may be 1.0 to 10 mass %, may be 2.0 to 7.0 mass %, or may be 3.0 to 5.0 mass %.
[0053] The total content of the first structural unit and the second structural unit in the copolymer (A) is preferably 65% by mass or more, more preferably 75% by mass or more, even more preferably 85% by mass or more, and may be 90% by mass or more. This is because it is possible to suppress an increase in the glass transition point of the copolymer (A) and improve the tackiness, wettability, and even adhesion of the adhesive layer. The total content of the first structural unit and the second structural unit in the copolymer (A) may be 95% by mass or more, 100% by mass, or 100% by mass or less.
[0054] The content of structural units derived from octyl(meth)acrylate in the copolymer (A) is preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 40% by mass or more, because the adhesive layer obtained from the adhesive composition containing the copolymer (A) has improved adhesive strength in a high-temperature environment.
[0055] The content of structural units derived from octyl (meth)acrylate in the copolymer (A) may be 90% by mass or less, 80% by mass or less, or 70% by mass or less.
[0056] The content of structural units derived from octyl (meth)acrylate in the copolymer (A) may be from 20 to 90% by mass, from 30 to 80% by mass, or from 40 to 70% by mass.
[0057] The content of structural units derived from 2-octyl(meth)acrylate in the copolymer (A) is preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 40% by mass or more, because the adhesive layer obtained from the adhesive composition containing the copolymer (A) has improved adhesive strength in a high-temperature environment.
[0058] The content of structural units derived from 2-octyl (meth)acrylate in the copolymer (A) may be 90% by mass or less, 80% by mass or less, or 70% by mass or less.
[0059] The content of structural units derived from 2-octyl (meth)acrylate in the copolymer (A) may be 20 to 90 mass %, 30 to 80 mass %, or 40 to 70 mass %.
[0060] (1-5. Glass transition temperature of copolymer (A)) The glass transition temperature Tg of copolymer (A) is calculated by the Fox formula based on the glass transition temperature when each structural unit contained in copolymer (A) is treated as a homopolymer. The specific method of calculating the glass transition temperature Tg of copolymer (A) is calculated by the Fox formula 1 / Tg=Σ(Xi / Tgi) from the glass transition temperature Tgi of the homopolymer of each structural unit Mi (i=1,2,3...,) and the mass fraction Xi of structural unit Mi in copolymer (A) (ΣXi (total structural units)=1).
[0061] In the Fox formula, Tg and Tgi are both calculated as absolute temperature (K) values. Here, by converting 0°C = 273.15K, the glass transition point Tg of the copolymer (A) can be calculated as Celsius temperature.
[0062] The glass transition temperature Tg of each homopolymer is a value described in the literature "Polymer Handbook (3rd Edition, John Wiley & Sons, Inc., 1989)". The glass transition temperature Tg of a homopolymer not described in the literature is the peak top temperature of a DDSC chart obtained as the temperature derivative of DSC measured by a differential scanning calorimetry (DSC) device (EXSTAR DSC / SS7020 manufactured by Hitachi High-Tech Science Corporation) at a heating rate of 10°C / min under a nitrogen gas atmosphere.
[0063] The glass transition point Tg of the copolymer (A) is preferably −80° C. or higher, more preferably −65° C. or higher, and even more preferably −55° C. or higher, because it improves the cohesive strength of the pressure-sensitive adhesive formed using the copolymer (A) and can impart superior holding power at high temperatures to the pressure-sensitive adhesive layer.
[0064] The glass transition point Tg of the copolymer (A) is preferably 30° C. or lower, more preferably 0° C. or lower, even more preferably −20° C. or lower, and even more preferably −30° C. or lower. This is because the wettability of the adhesive composition formed using the copolymer (A) can be improved, and the adhesiveness of the adhesive layer to the substrate can be improved. In addition, the flexibility of the adhesive layer formed using the copolymer (A) can be increased, and the tackiness of the adhesive layer when used dry can be improved.
[0065] The glass transition point Tg of the copolymer (A) may be from -80 to 30°C, from -65 to 0°C, from -55 to -20°C, or from -55 to -30°C.
[0066] <2. Method for producing copolymer> The method for producing copolymer (A) according to the present embodiment includes a step of emulsion polymerizing a monomer (hereinafter also referred to as "raw material monomer for copolymer (A)") containing an alkyl(meth)acrylate and an ethylenically unsaturated compound having at least one selected from the group consisting of a carboxy group and a salt of a carboxy group, and the alkyl(meth)acrylate contains octyl(meth)acrylate.
[0067] By producing the copolymer (A) by emulsion polymerization, it is possible to obtain a high molecular weight copolymer (A). The high molecular weight copolymer (A) can improve the cohesive strength of the adhesive and impart superior holding power at high temperatures to the adhesive layer. In addition, since emulsion polymerization can be carried out in an aqueous medium as described below, the environmental impact of production is small.
[0068] (2-1: Monomer) The alkyl (meth)acrylate and the ethylenically unsaturated compound having at least one selected from the group consisting of a carboxy group and a salt of a carboxy group contained in the raw material monomers of copolymer (A) can be explained in the same manner as the alkyl (meth)acrylate from which the first structural unit of copolymer (A) of this embodiment is derived and the ethylenically unsaturated compound having at least one selected from the group consisting of a carboxy group and a salt of a carboxy group from which the second structural unit is derived, and the preferred embodiments are also the same.
[0069] (2-2: Emulsion polymerization process) The production method of this embodiment includes a step of emulsion polymerizing a monomer including an alkyl(meth)acrylate and an ethylenically unsaturated compound having at least one member selected from the group consisting of a carboxy group and a salt of a carboxy group.
[0070] The content of alkyl (meth)acrylate in the total amount (100% by mass) of raw material monomers of copolymer (A) is preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, because this can suppress an increase in the glass transition point of the resulting copolymer (A) and improve the tackiness, wettability, and adhesion of the adhesive layer.
[0071] The content of alkyl (meth)acrylate in the total amount (100% by mass) of raw material monomers of copolymer (A) is preferably 99% by mass or less, more preferably 98% by mass or less, and even more preferably 97% by mass or less, because the polarity of the resulting copolymer (A) and the cohesive strength of the adhesive layer are kept at a moderate level, and an adhesive layer having high adhesiveness not only at room temperature but also at high and low temperatures is obtained.
[0072] The content of alkyl (meth)acrylate in the total amount (100 mass%) of raw material monomers of the copolymer (A) may be 60 to 99 mass%, 70 to 98 mass%, or 80 to 97 mass%.
[0073] The content of the ethylenically unsaturated compound having at least one selected from the group consisting of a carboxy group and a salt of a carboxy group in the total amount (100% by mass) of the raw material monomers of the copolymer (A) is preferably 1.0% by mass or more, more preferably 2.0% by mass or more, and even more preferably 3.0% by mass or more, because this can improve the cohesive strength of the resulting adhesive layer containing the copolymer (A) and increase the holding power at high temperatures.
[0074] The content of the ethylenically unsaturated compound having at least one selected from the group consisting of a carboxy group and a salt of a carboxy group in the total amount (100% by mass) of the raw material monomers of the copolymer (A) is preferably 10% by mass or less, more preferably 7.0% by mass or less, and even more preferably 5.0% by mass or less, because this can suppress an increase in the glass transition point of the resulting copolymer (A) and improve the tackiness, wettability, and further adhesive strength of the adhesive layer.
[0075] The content of the ethylenically unsaturated compound having at least one selected from the group consisting of a carboxy group and a salt of a carboxy group in the total amount (100 mass%) of raw material monomers of the copolymer (A) may be 1.0 to 10 mass%, may be 2.0 to 7.0 mass%, or may be 3.0 to 5.0 mass%.
[0076] The total content of the alkyl (meth)acrylate and the ethylenically unsaturated compound having at least one selected from the group consisting of a carboxyl group and a salt of a carboxyl group in the total amount (100% by mass) of the raw material monomers of the copolymer (A) is preferably 65% by mass or more, more preferably 75% by mass or more, and even more preferably 85% by mass or more. This can suppress an increase in the glass transition point of the resulting copolymer (A) and can further improve the tackiness, wettability, and adhesion of the adhesive layer. The total content of the alkyl (meth)acrylate and the ethylenically unsaturated compound having at least one selected from the group consisting of a carboxy group and a salt of a carboxy group in the total amount (100 mass%) of raw material monomers of the copolymer (A) may be 90 mass% or more, 100 mass% or less, or may be 100 mass% or less.
[0077] The content of octyl (meth)acrylate in the total amount (100 mass%) of raw material monomers of copolymer (A) is preferably 20 mass% or more, more preferably 30 mass% or more, and even more preferably 40 mass% or more, because the adhesive layer obtained from the adhesive composition containing copolymer (A) has improved adhesive strength in a high-temperature environment.
[0078] The content of octyl (meth)acrylate in the total amount (100% by mass) of raw material monomers of the copolymer (A) may be 90% by mass or less, 80% by mass or less, or 70% by mass or less.
[0079] The content of octyl (meth)acrylate in the total amount (100% by mass) of raw material monomers of the copolymer (A) may be 20 to 90% by mass, 30 to 80% by mass, or 40 to 70% by mass.
[0080] The content of 2-octyl(meth)acrylate in the total amount (100% by mass) of raw material monomers of copolymer (A) is preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 40% by mass or more, because the adhesive layer obtained from the adhesive composition containing copolymer (A) has improved adhesive strength in a high-temperature environment.
[0081] The content of 2-octyl (meth)acrylate in the total amount (100 mass%) of raw material monomers of the copolymer (A) may be 90 mass% or less, 80 mass% or less, or 70 mass% or less.
[0082] The content of 2-octyl (meth)acrylate in the total amount (100% by mass) of raw material monomers of the copolymer (A) may be 20 to 90% by mass, 30 to 80% by mass, or 40 to 70% by mass.
[0083] In the emulsion polymerization, a polymerization initiator for accelerating the polymerization reaction, a chain transfer agent for controlling the molecular weight and molecular weight distribution of the copolymer (A) within an appropriate range, an emulsifier for emulsifying the monomers, etc. may be used. The raw material monomers of the copolymer (A) may be charged in advance in their entirety into the reactor, or may be polymerized while being continuously or intermittently fed from the viewpoint of obtaining uniform particles. The raw material monomers fed continuously or intermittently may be a part or all of the raw material monomers of the copolymer (A). The polymerization temperature is not particularly limited, but is preferably 5 to 100°C, more preferably 50 to 90°C.
[0084] In the production method of this embodiment, the emulsion polymerization of the monomers is preferably carried out in an aqueous medium, thereby obtaining a copolymer-containing liquid (copolymer dispersion) in which the copolymer (A) is dispersed as emulsified particles in the aqueous medium, i.e., an emulsion. The aqueous medium is water, a hydrophilic organic solvent, or a mixture thereof. Examples of the hydrophilic organic solvent include methanol, ethanol, isopropyl alcohol, and N-methylpyrrolidone. From the viewpoint of polymerization stability, the aqueous medium is preferably water. In addition, as long as the polymerization stability is not impaired, a mixed solvent of water and a hydrophilic solvent may be used as the aqueous medium.
[0085] Examples of the polymerization initiator include persulfate-based initiators such as potassium persulfate and ammonium persulfate; water-soluble azo-based initiators such as 2,2'-azobis(2-methylpropionamidine) dihydrochloride; organic peroxides such as t-butyl hydroperoxide and cumene hydroperoxide; and hydrogen peroxide. Only one type of polymerization initiator may be used, or two or more types may be used. The amount of the polymerization initiator used is not particularly limited, but is preferably 0.1 to 2.0 parts by mass relative to 100 parts by mass of the total amount of the raw material monomers of the copolymer (A).
[0086] If necessary, a reducing agent can be used together with the polymerization initiator. Examples of such reducing agents include reducing organic compounds such as ascorbic acid, tartaric acid, citric acid, glucose, and formaldehyde sulfoxylate metal salts; reducing inorganic compounds such as sodium thiosulfate, sodium sulfite, sodium bisulfite, and sodium metabisulfite. Only one type of reducing agent may be used, or two or more types may be used.
[0087] Examples of the chain transfer agent include n-dodecyl mercaptan, t-dodecyl mercaptan, n-butyl mercaptan, 2-ethylhexyl thioglycolate, 2-mercaptoethanol, β-mercaptopropionic acid, methyl alcohol, n-propyl alcohol, isopropyl alcohol, t-butyl alcohol, benzyl alcohol, etc. Only one type of chain transfer agent may be used, or two or more types may be used.
[0088] The amount of the chain transfer agent used is preferably 5.0 parts by mass or less, more preferably 2.0 parts by mass or less, even more preferably 0.50 parts by mass or less, and even more preferably 0.30 parts by mass or less, based on 100 parts by mass of the total amount of the raw material monomers of the copolymer (A), because the cohesive strength of the pressure-sensitive adhesive is improved, and the holding power of the pressure-sensitive adhesive layer at high temperatures can be improved. The amount of the chain transfer agent used may be 0.01 parts by mass or more, or may be 0.05 parts by mass or more, based on 100 parts by mass of the total amount of the monomers, because the adhesive strength of the adhesive layer can be improved.
[0089] Examples of emulsifiers include anionic surfactants such as sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, and sodium polyoxyethylene alkyl ether sulfate; nonionic surfactants such as polyoxyethylene alkyl ether and polyoxyethylene nonylphenyl ether; cationic surfactants such as sesyltrimethylammonium bromide and laurylpyridinium chloride; amphoteric surfactants such as lauryl betaine; and the above-mentioned polymerizable surfactants. Only one type of these surfactants may be used, or two or more types may be used. The amount of the emulsifier used is not particularly limited, but is preferably 0.1 to 6.0 parts by mass, and more preferably 1.0 to 4.0 parts by mass, per 100 parts by mass of the total amount of the monomers. In calculating the content of each structural unit of copolymer (A), the polymerizable surfactant is classified as a monomer of copolymer (A) and its presence is taken into consideration, whereas emulsifiers other than polymerizable surfactants are not classified as monomers of copolymer (A) and their presence is ignored.
[0090] <3. Pressure-sensitive adhesive composition> The pressure-sensitive adhesive composition according to this embodiment contains the copolymer (A) according to this embodiment and an aqueous medium (hereinafter also referred to as "aqueous medium (B)"). The pressure-sensitive adhesive composition according to this embodiment may contain other additives. The pressure-sensitive adhesive composition of the present embodiment may be in the form of a solution, a dispersion (for example, an emulsion), a slurry, or the like, but is not limited thereto.
[0091] In the pressure-sensitive adhesive composition, the copolymer (A) is preferably dispersed as particles in an aqueous medium to form an emulsion.
[0092] (3-1. Aqueous medium (B)) The aqueous medium (B) is water, a hydrophilic organic solvent, or a mixture thereof. Examples of the hydrophilic organic solvent include methanol, ethanol, isopropyl alcohol, and N-methylpyrrolidone. Among these, the aqueous medium (B) is preferably water. The aqueous medium (B) may have the same composition as the aqueous medium used in the polymerization of the copolymer (A), or may have a different composition. Only one type of aqueous medium (B) may be used, or two or more types may be used.
[0093] (3-2. Other Additives) As the other additives, for example, a pH adjuster, a tackifier, a plasticizer, an antioxidant, a filler, a pigment, a colorant, a wetting agent, an antifoaming agent, a thickener, a crosslinking agent, etc. may be appropriately used. Only one type of the other additives may be used, or two or more types may be used.
[0094] Examples of tackifiers include rosin resins, rosin ester resins, hydrogenated rosin resins, polymerized rosin resins, α-pinene resins, β-pinene resins, terpene phenol resins, C5 fraction petroleum resins, C9 fraction petroleum resins, C5 fraction / C9 fraction petroleum resins, dicyclopentadiene petroleum resins, alkylphenol resins, xylene resins, coumarone resins, coumarone indene resins, etc. Only one type of tackifier may be used, or two or more types may be used.
[0095] (3-3. Non-volatile content of adhesive composition, etc.) The non-volatile content of the adhesive composition is preferably 20% by mass or more, more preferably 40% by mass or more, and even more preferably 60% by mass or more. This is because a larger amount of adhesive layer can be formed with a smaller amount of adhesive composition applied. In addition, the drying time of the applied adhesive composition is shortened, and the productivity is improved. The "non-volatile content" of the adhesive composition refers to the components remaining after weighing 1 g of the adhesive composition onto an aluminum dish with a diameter of 5 cm and drying it for 1 hour at 105°C while circulating air in a dryer at 1 atmosphere (1013 hPa). The "non-volatile content concentration" of the adhesive composition refers to the mass ratio (mass%) of the non-volatile content after drying under the above conditions to the mass (1 g) of the adhesive composition before drying.
[0096] The non-volatile content of the pressure-sensitive adhesive composition is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 75% by mass or less, because this makes it possible to more effectively suppress gelation of the copolymer (A) in the pressure-sensitive adhesive composition.
[0097] The nonvolatile content concentration of the pressure-sensitive adhesive composition may be 20 to 90% by mass, 40 to 80% by mass, or 60 to 75% by mass.
[0098] The content of copolymer (A) in the non-volatile matter of the pressure-sensitive adhesive composition is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, because the adhesive layer containing copolymer (A) has improved adhesive strength and holding power, particularly holding power at high temperatures.
[0099] The content of copolymer (A) in the nonvolatile matter of the pressure-sensitive adhesive composition is preferably 99.5% by mass or less, and more preferably 99% by mass or less, because the adhesive strength and holding power of the adhesive layer containing copolymer (A), particularly the adhesive strength at room temperature and high temperature, are improved.
[0100] The content of the copolymer (A) in the non-volatile matter of the pressure-sensitive adhesive composition may be 50 to 99.5% by mass, 60 to 99% by mass, or 70 to 99% by mass.
[0101] 3-4. Size of particles in pressure-sensitive adhesive composition The particles in the pressure-sensitive adhesive composition are particles dispersed in the aqueous medium (B). The average particle size of the particles in the pressure-sensitive adhesive composition is a value measured by NANOTRAC WAVE II (manufactured by MicrotracBEL). The average particle size of the aqueous resin composition dispersed in the aqueous medium is preferably 10 nm or more, more preferably 50 nm or more, even more preferably 100 nm or more, and even more preferably 200 nm or more. This is because the particles can be more stably dispersed in the aqueous medium (B).
[0102] The average particle size of the particles in the pressure-sensitive adhesive composition is preferably 50,000 nm or less, more preferably 10,000 nm or less, even more preferably 1,000 nm or less, even more preferably 500 nm or less, and particularly preferably 350 nm or less, because this can increase the density of the pressure-sensitive adhesive layer obtained from the pressure-sensitive adhesive composition and improve the heat resistance of the pressure-sensitive adhesive layer during dry use.
[0103] The average particle size of the particles in the pressure-sensitive adhesive composition may be 10 to 50,000 nm, 50 to 10,000 nm, 100 to 1,000 nm, 100 to 500 nm, or 200 to 350 nm.
[0104] (3-5. Method for producing pressure-sensitive adhesive composition) The method for producing the pressure-sensitive adhesive composition of the present embodiment is not particularly limited, and may be, for example, a method in which the above-mentioned other additives used as necessary are added to an emulsion containing emulsion particles containing copolymer (A) and water, and mixed. The timing of adding the other additives is not particularly limited.
[0105] <3-6. Products to which the adhesive composition is applied> The pressure-sensitive adhesive composition of the present embodiment is not particularly limited, and can be used, for example, in pressure-sensitive adhesive tapes, pressure-sensitive adhesive sheets, pressure-sensitive adhesive labels, stickers, liquid pressure-sensitive adhesives, and the like.
[0106] <4. Adhesive layer and adhesive tape> The pressure-sensitive adhesive layer of the present embodiment is an adhesive layer formed using the pressure-sensitive adhesive composition of the present embodiment. The pressure-sensitive adhesive layer of the present embodiment is formed on a substrate, for example, by applying the pressure-sensitive adhesive composition of the present embodiment to the substrate, drying the composition, and, if necessary, allowing a crosslinking reaction to occur. The drying conditions after the pressure-sensitive adhesive composition of the present embodiment is applied to a substrate are not particularly limited, but for example, drying conditions of 1 to 5 minutes at 80 to 110° C. After drying, the composition may be allowed to stand at 20 to 50° C. for one day or more, if necessary. The nonvolatile content of the adhesive layer is preferably 95% by mass or more, more preferably 97% by mass or more, and even more preferably 99% by mass or more, and may be 100% by mass. The thickness of the adhesive layer is not particularly limited, but may be 5 to 200 μm, 10 to 100 μm, or 20 to 50 μm.
[0107] The pressure-sensitive adhesive tape of the present embodiment comprises a substrate and an adhesive layer formed on the surface of the substrate, the adhesive layer being formed using the pressure-sensitive adhesive composition of the present embodiment. The adhesive layer may be formed on only one surface of the substrate, or on both surfaces. The substrate is not particularly limited, but examples thereof include resin films such as polyethylene terephthalate (PET) films; woven fabrics; nonwoven fabrics; and metal foils. The adhesive tape may have other layers (e.g., an intermediate layer, an undercoat layer, etc.) in addition to the substrate and the adhesive layer, as long as the effects of the invention are not impaired. In addition, the adhesive layer of the adhesive tape may be protected by a known release liner such as release paper or release PET. The adhesive tape of this embodiment is explained in the same manner as the manufacturing method of the adhesive layer of this embodiment described above.
[0108] <5. Uses of the adhesive composition, adhesive layer, and adhesive tape> The pressure-sensitive adhesive composition, pressure-sensitive adhesive layer, and pressure-sensitive adhesive tape of the present embodiment can be used in various applications and fields such as packaging, bonding, fixing, protection, decoration, transportation, etc. Furthermore, the material of the object (adherend) on which the pressure-sensitive adhesive composition, pressure-sensitive adhesive layer, and pressure-sensitive adhesive tape of the present embodiment are provided is not particularly limited, and examples thereof include plastic, metal, glass, wood, ceramics, paper, cloth, etc., and the pressure-sensitive adhesive composition, pressure-sensitive adhesive layer, and pressure-sensitive adhesive tape of the present embodiment can be used in a wide range of applications. EXAMPLES
[0109] Examples and comparative examples of this embodiment will be described below, but this embodiment is not limited to these examples.
[0110] <1. Preparation of copolymer and pressure-sensitive adhesive composition> Example 1 Copolymer (A) was synthesized by emulsion polymerization in water, specifically as follows.
[0111] In a polymerization apparatus equipped with a stirrer, a thermometer, and a reflux condenser, 23 parts by mass of ion-exchanged water was heated to 80° C. under a nitrogen atmosphere. The ion-exchanged water in the polymerization apparatus was kept at 80° C. while being stirred, and 2.0 parts by mass of a 5.0% by mass aqueous potassium persulfate solution was added as a polymerization initiator to obtain a mixed solution containing the polymerization initiator.
[0112] A monomer emulsion containing 20 parts by mass of ion-exchanged water, "ADEKA REASOAP SR-10" (trade name, manufactured by ADEKA Corporation, ether sulfate type ammonium salt, polymerizable surfactant) and "LATEMUL E-118B" (trade name, manufactured by Kao Corporation, polyoxyethylene alkyl ether sodium sulfate) in the amounts shown in Table 1 as emulsifiers, and monomers and chain transfer agents in the types and amounts shown in Table 1 was dropped into the mixture containing the polymerization initiator in the polymerization apparatus over a period of 4 hours. Simultaneously with the start of dropping the monomer emulsion, 20 parts by mass of a 2.5% by mass potassium persulfate aqueous solution was dropped over a period of 4 hours. During the dropping of the monomer emulsion, the mixture in the polymerization apparatus was stirred at 120 revolutions per minute, and the liquid temperature was maintained at 80°C. After the dropping was completed, the mixture was reacted at 80°C for 1 hour while continuing to stir.
[0113] Thereafter, the mixed liquid in the polymerization apparatus was cooled to 25° C. Ammonia water was added as a neutralizing agent to adjust the pH to 7.0, thereby obtaining an emulsion containing water and emulsified particles containing the copolymer (A).
[0114] To 100 parts by mass of the obtained emulsion, 2.0 parts by mass of "ADEKA NOL UH-420" (product name, manufactured by ADEKA CORPORATION, nonionic thickener) was added as a thickener to obtain a pressure-sensitive adhesive composition.
[0115] (Examples 2 to 4) Copolymers and pressure-sensitive adhesive compositions of Examples 2 to 4 were obtained in the same manner as in Example 1, except that the monomers and chain transfer agent were blended as shown in Table 1.
[0116] (Comparative Examples 1 to 2) Copolymers and pressure-sensitive adhesive compositions of Comparative Examples 1 and 2 were obtained in the same manner as in Example 1, except that the monomers and chain transfer agent were blended as shown in Table 1.
[0117] Comparative Example 3 In Comparative Example 3, the copolymer was prepared in toluene by a solution polymerization process. Specifically, a mixed solution containing 120 parts by mass of toluene and the types and amounts of monomers and chain transfer agents in Table 1 was heated to 70°C under a nitrogen atmosphere in a polymerization apparatus equipped with a stirrer, a thermometer, and a reflux condenser. The mixed solution in the polymerization apparatus was kept at 70°C while stirring, and 1.0 part by mass of 2,2'-azobisisobutyronitrile was added as a polymerization initiator. The mixed solution was reacted at 70°C for 5 hours while stirring, and then the mixed solution in the polymerization apparatus was cooled to 25°C to obtain a copolymer. During and after the above reaction, the monomer and the copolymer, which is the product, were in a state of being uniformly dissolved in the solvent. The subsequent steps were carried out in the same manner as in Example 1 to obtain a pressure-sensitive adhesive composition of Comparative Example 3.
[0118] Comparative Example 4 In Comparative Example 4, the copolymer was prepared in water by a suspension polymerization process. Specifically, in a polymerization apparatus equipped with a stirrer, a thermometer, and a reflux condenser, a mixed solution containing 80 parts by mass of ion-exchanged water, "ADEKA REASOAP SR-10" (trade name, manufactured by ADEKA Corporation, ether sulfate type ammonium salt, polymerizable surfactant) and "LATEMURU E-118B" (trade name, manufactured by Kao Corporation, polyoxyethylene alkyl ether sodium sulfate) in the amounts shown in Table 1 as emulsifiers, and a total of 100 parts by mass of monomers and chain transfer agents in the formulations shown in Table 1 was mixed at 350 revolutions per minute for 30 minutes to obtain a monomer droplet diameter of about 50 μm. The temperature was raised to 70° C. under a nitrogen atmosphere, and the mixed solution in the polymerization apparatus was kept at 70° C. while stirring, and 0.2 parts by mass of 2,2'-azobisisobutyronitrile was added as a polymerization initiator. The mixed solution in the polymerization apparatus was reacted at 70° C. for 5 hours with stirring, and then the mixed solution in the polymerization apparatus was cooled to 25° C. to obtain a copolymer and pressure-sensitive adhesive composition of Comparative Example 4.
[0119] Comparative Example 5 When the same procedure as in Comparative Example 4 was carried out except that the monomer and chain transfer agent were blended as shown in Table 1, aggregates were generated during the reaction, and no pressure-sensitive adhesive composition was obtained.
[0120] <2. Measurement of non-volatile content of adhesive composition> 1 g of the adhesive composition was weighed onto an aluminum dish with a diameter of 5 cm, and the composition was dried at 105°C for 1 hour while circulating air in a dryer at 1 atmosphere (1013 hPa), and the mass of the remaining non-volatile content was measured. The mass ratio of the non-volatile content after drying under the above conditions to the mass (1 g) of the adhesive composition before drying was calculated as the non-volatile content concentration (mass%) of the adhesive composition.
[0121] <3. Preparation of adhesive tape> The adhesive compositions obtained in Examples 1 to 4 and Comparative Examples 1 to 4 were applied to a PET film (A4 size, thickness 50 μm). A doctor blade with a coating width of 15 cm was used as the applicator. The applied adhesive composition was dried at 100° C. for 2 minutes, and the aqueous medium was removed from the adhesive composition to form an adhesive layer with a thickness of 30 μm on the PET film. The release surface (silicone-coated surface) of release paper was attached to the adhesive layer on the PET film, and then cured at 23° C. for 1 day to obtain an adhesive tape comprising a substrate and an adhesive layer formed on the substrate, with the release paper attached to the adhesive layer.
[0122] <4. Evaluation of adhesive tape> The pressure-sensitive adhesive tapes produced in each of the Examples and Comparative Examples were subjected to the following evaluations 1 to 3. In the following description, the procedures in each of the Examples and Comparative Examples are common unless otherwise specified.
[0123] [4-1. Evaluation 1: Measurement of adhesive strength at room temperature (room temperature adhesive strength)] The release paper of the adhesive tape was cut into a tape width of 25 mm and a length of 100 mm, and half of the tape was peeled off in the longitudinal direction. The tape was then attached to a SUS#304 plate to prepare a sample for evaluation. The lamination was performed by moving a 2 kg roller back and forth once in an atmosphere of 23° C. The atmospheric temperature during lamination in the preparation of the evaluation sample is hereinafter referred to as the lamination temperature. (Lamination temperature in evaluation 1: 23° C.) In the evaluation sample, the portion where the adhesive tape and the SUS#304 plate were bonded was a rectangle of 25 mm x 50 mm. None of the ends of the bonded portion of the adhesive tape were overlapped with the ends of the SUS#304 plate. In other words, in this state, half of one end of the adhesive tape in the longitudinal direction was bonded to the SUS#304 plate, and half of the other end was bonded to the release paper.
[0124] After the evaluation sample was prepared, it was left to stand for 30 minutes in an atmosphere at a temperature of 23° C. The atmospheric temperature during standing after the preparation of the evaluation sample is hereinafter referred to as the standing temperature. (Standing temperature in evaluation 1: 23° C.) Thereafter, the following measurements were performed in an atmosphere at a temperature of 23° C. The measurement temperature of the evaluation sample is hereinafter referred to as the measurement temperature. (Measurement temperature in evaluation 1: 23° C.)
[0125] The test was a so-called 180° peel test. The adhesive tape of the evaluation sample was folded back 180°, with the boundary between the part attached to the SUS#304 plate and the part not attached as the folding line. One end of the adhesive tape on the side not attached to the SUS#304 plate (the folded end) was held by the upper chuck of the testing machine (Tensilon RTG-1210 (manufactured by A&D Co., Ltd.)). One end of the SUS#304 plate facing the upper chuck across the folding line was held by the lower chuck.
[0126] In this state, the adhesive tape was peeled off from the SUS#304 plate at a speed of 300 mm / min to obtain a graph of peel length (mm) vs. peel force (N). In the graph obtained, the average peel force (N) at a peel length of 25 to 50 mm (the graph area at a peel length of 25 to 50 mm divided by the peel length) was calculated, and this value was defined as the room temperature adhesive strength (N / 25 mm).
[0127] [4-2. Evaluation 2: Measurement of adhesive strength under high temperature environment (high temperature adhesive strength)] The adhesive strength (N / 25 mm) in a high temperature environment was measured in the same manner as in "Evaluation 1" above, except that the standing temperature was 70°C and the measurement temperature was 70°C.
[0128] [4-3. Evaluation 3: Measurement of high temperature retention] The release paper of the adhesive tape cut to a tape width of 25 mm and a length of 100 mm was peeled off 25 mm from one end in the longitudinal direction, and a SUS plate (SUS#304) was attached to cover the entire area from which the release paper had been peeled off, to prepare an evaluation sample. That is, in the evaluation sample, the area where the adhesive tape and the SUS plate were attached was a square of 25 mm x 25 mm. The attachment was performed by moving a 2 kg roller back and forth once in an atmosphere of 23°C. In addition, at this time, the portion of the SUS plate alone, where the adhesive tape was not attached, on the extension of one end of the adhesive tape attached to the SUS plate, was provided as a chuck part on the SUS plate side.
[0129] The evaluation sample was left to stand in a thermostatic chamber at 80°C for 30 minutes. After that, the chuck part of the evaluation sample on the SUS plate side was held by a chuck in the thermostatic chamber at 80°C, and a 1 kg weight was hung from one end of the adhesive tape in the longitudinal direction on the side where the SUS plate was not attached, and the time (h) it took for the weight to fall was measured. The test was carried out for up to 24 hours, and those in which the weight had not fallen after 24 hours were recorded as "24<" in Table 1.
[0130] <5. Evaluation Results> The results of evaluations 1 to 3 are shown in Table 1. The average particle size of the particles in the pressure-sensitive adhesive composition in Table 1 is a value measured using a NANOTRAC WAVE II (manufactured by MicrotracBEL).
[0131] [Table 1]
[0132] As shown in Table 1, the adhesive tapes of Examples 1 to 4, which use copolymer (A) containing a structural unit derived from octyl (meth)acrylate in this embodiment, exhibit strong adhesive strength not only at room temperature but also at high temperatures, and form an adhesive layer that also has high holding power at high temperatures.
[0133] On the other hand, in the adhesive tapes of Comparative Example 1 and Comparative Example 2, which were made from adhesive compositions using copolymers that did not contain structural units derived from octyl (meth)acrylate, at least one of the adhesive strength and high-temperature retention strength was insufficient.
[0134] From these facts, it is understood that the object of this embodiment cannot be achieved with a copolymer that does not contain a structural unit derived from octyl (meth)acrylate.
[0135] Moreover, the adhesive tape according to Comparative Example 3, which was produced using an adhesive composition using a copolymer produced by solution polymerization, did not have sufficient high-temperature adhesive strength. Moreover, the adhesive tape according to Comparative Example 4, which was produced using an adhesive composition using a copolymer produced by suspension polymerization, did not have sufficient adhesive strength and high-temperature retention.
[0136] From these facts, it is understood that the object of this embodiment cannot be achieved in a configuration in which the copolymer is produced by a method other than emulsion polymerization.
[0137] As described above, according to the present embodiment, it is possible to provide a copolymer and a pressure-sensitive adhesive composition capable of forming an adhesive layer that exhibits strong adhesive strength not only at room temperature but also at high temperatures, and further has high holding power at high temperatures. Furthermore, according to the present embodiment, it is possible to provide an adhesive layer that exhibits strong adhesive strength not only at room temperature but also at high temperatures, and that also has high holding power at high temperatures, and an adhesive tape including such an adhesive layer.
Claims
1. A pressure-sensitive adhesive composition comprising a copolymer obtained by emulsion polymerization and an aqueous medium, The copolymer is A first structural unit derived from an alkyl (meth)acrylate; a second structural unit derived from an ethylenically unsaturated compound having at least one selected from the group consisting of a carboxy group and a salt of a carboxy group; A structural unit derived from a vinyl ester compound; having The first structural unit includes a structural unit derived from octyl (meth)acrylate, A pressure-sensitive adhesive composition, wherein the content of structural units derived from 2-octyl(meth)acrylate among the structural units contained as the first structural units is 45 to 70 mass %.
2. The pressure-sensitive adhesive composition according to claim 1, wherein the copolymer has a content of the second structural unit of 1.0 to 10 mass %.
3. The pressure-sensitive adhesive composition according to claim 1, wherein the first structural unit further comprises at least one selected from the group consisting of a structural unit derived from methyl (meth)acrylate, a structural unit derived from n-butyl (meth)acrylate, and a structural unit derived from 2-ethylhexyl (meth)acrylate.
4. The pressure-sensitive adhesive composition according to claim 1 , wherein the copolymer is dispersed as particles in the aqueous medium to form an emulsion.
5. The pressure-sensitive adhesive composition according to claim 1, wherein the particles dispersed in the aqueous medium have an average particle size of 10 to 50,000 nm.
6. The adhesive tape has a substrate and an adhesive layer formed on a surface of the substrate, An adhesive tape, wherein the adhesive layer is formed using the adhesive composition according to claim 1.
7. A method for producing a copolymer in the pressure-sensitive adhesive composition according to any one of claims 1 to 5, comprising the steps of: The method includes a step of emulsion polymerizing a monomer including an alkyl (meth)acrylate and an ethylenically unsaturated compound having at least one member selected from the group consisting of a carboxy group and a salt of a carboxy group, The method for producing a copolymer, wherein the alkyl (meth)acrylate includes 2-octyl (meth)acrylate.
8. The method for producing a copolymer according to claim 7, wherein the content of 2-octyl (meth)acrylate in the monomer is 20 to 90% by mass.
Citation Information
Patent Citations
Acrylic polymer and resin composition containing the same polymer
JP1998231325A
Acrylic emulsion type pressure-sensitive adhesive and pressure-sensitive adhesive product using the same
JP2000119617A
Tape for fixing floor curing sheet
JP2002105421A
Pressure sensitive adhesive containing silica nanoparticles
JP2009529089A
2-Octyl (meth)acrylate adhesive composition
JP2011516690A